Mechanisms of Direct and Indirect Presentation of Self-Antigens in the Thymus - Březina, Jiří; Vobořil, Matouš; Filipp, Dominik (Frontiers in Immunology, 2022)
The inevitability of evolution of the adaptive immune system with its mechanism of randomly rearranging segments of the T cell receptor (TCR) gene is the generation of self-reactive clones. For the sake of prevention of autoimmunity, these clones must be eliminated from the pool of circulating T cells. This process occurs largely in the thymic medulla where the strength of affinity between TCR and self-peptide MHC complexes is the factor determining thymocyte fate. Thus, the display of self-antigens in the thymus by thymic antigen presenting cells, which are comprised of medullary thymic epithelial (mTECs) and dendritic cells (DCs), is fundamental for the establishment of T cell central tolerance. Whereas mTECs produce and present antigens in a direct, self-autonomous manner, thymic DCs can acquire these mTEC-derived antigens by cooperative antigen transfer (CAT), and thus present them indirectly. While the basic characteristics for both direct and indirect presentation of self-antigens are currently known, recent reports that describe the heterogeneity of mTEC and DC subsets, their presentation capacity, and the potentially non-redundant roles in T cell selection processes represents another level of complexity which we are attempting to unravel. In this review, we underscore the seminal studies relevant to these topics with an emphasis on new observations pertinent to the mechanism of CAT and its cellular trajectories underpinning the preferential distribution of thymic epithelial cell-derived self-antigens to specific subsets of DC. Identification of molecular determinants which control CAT would significantly advance our understanding of how the cellularly targeted presentation of thymic self-antigens is functionally coupled to the T cell selection process.